2005
DOI: 10.1177/175045890501500603
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Equipment and Materials Left in Patients

Abstract: This article seeks to examine the issue of lost equipment and materials left in patients and the assumptions that registered theatre practitioners make. The assumptions are highlighted using a tragic case study that relates to a young lady who died and what the subsequent post mortem revealed: five pieces of gauze in her abdominal cavity which were proved to be five surgical swabs. The problem of retained swabs and other surgical equipment is far greater than many would believe. It is said 'to err is human', b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…2 The real incidence is likely to be very much higher; Brown and colleagues estimated the incidence in the United States (US) to be 1 in 1500 cases. 3 Australia's 2020 rate for a foreign body left behind after a procedure was 7.6 per 100,000 separations, higher than the Organisation for Economic Co-operation and Development (OECD) average of five. 4 Between 2012 and 2019 Australia had an annual rate of 22-34 cases of retained items.…”
Section: Introductionmentioning
confidence: 88%
“…2 The real incidence is likely to be very much higher; Brown and colleagues estimated the incidence in the United States (US) to be 1 in 1500 cases. 3 Australia's 2020 rate for a foreign body left behind after a procedure was 7.6 per 100,000 separations, higher than the Organisation for Economic Co-operation and Development (OECD) average of five. 4 Between 2012 and 2019 Australia had an annual rate of 22-34 cases of retained items.…”
Section: Introductionmentioning
confidence: 88%
“…Retained swabs and instruments could result in severe morbidity, and death from this incident has been reported. 34 An analysis 35 of claims in Chicago, USA, suggested that the incident occurred once in every 5000 operations. This is probably an under-estimate, as many cases pass unreported.…”
Section: Retained Swabs and Instrumentsmentioning
confidence: 99%
“…Currently, no law states how surgical teams should prevent RSIs or what methodologies they should use. The law, based on the doctrine of res ipsa locquitur (ie, the thing speaks for itself), does require that personnel be accountable for preventing RSIs and that surgical items not intended to remain in the patient be removed 6 . All members of the surgical team are accountable for preventing RSIs and providing safe care, and all can be held liable in cases of litigation resulting from an RSI.…”
mentioning
confidence: 99%